Mutants of Streptomyces coeruleorubidus impaired in the biosynthesis of daunomycinone glycosides and related metabolites - Blumauerová, M; Stajner, K; Pokorný, V; Hostálek, Z; Vanĕk, Z (Folia microbiologica, 1978)
Mutants of Streptomyces coeruleorubidus, blocked in the biosynthesis of anthracycline antibiotics of the daunomycine complex, were isolated from the production strains after treatment with UV light, gamma-radiation, nitrous acid, and after natural selection; according to their different biosynthetic activity the mutants were divided into five phenotypic groups. Mutants of two of these groups produced compounds that had not yet been described in Streptomyces coeruleorubidus (aklavinone, 7-deoxyaklavinone, zeta-rhodomycinone and glycosides of epsilon-rhodomycinone). The mutants differed from the parent strains and also mutually in morphological characteristics but no direct correlation between these changes and the biosynthetic activity could be observed in most cases.
Keywords: anthrachinony; Glycosides; daunomycin; mutace; Anthraquinones; Daunorubicin; Mutation; glykosidy; Streptomyces